Validity and reliability of lower‐limb pulse‐wave velocity assessments using an oscillometric technique. Issue 5 (25th March 2019) - Stone, Keeron; Fryer, Simon; Kelsch, Elizabeth; Burnet, Kathryn; Zieff, Gabriel; Faulkner, James; Credeur, Daniel; Lambrick, Danielle; Hanson, Erik D.; Stoner, Lee
Abstract : New Findings: What is the central question of this study? There is growing interest in the effects of sedentarism on central and peripheral cardiovascular health. To permit further investigation, including larger epidemiological studies, there is a need to identify arterial health assessment tools that are valid (accurate) and reliable (precise), yet practical. What is the main finding and its importance? Lower‐limb vascular health (femoral–ankle pulse‐wave velocity) can be determined in a supine position with accuracy and precision using an oscillometrically based device. This technology might help to improve our understanding of the pathological mechanisms linking cardiovascular disease to sedentarism, including the interaction between peripheral and central vasculature. Abstract: There is a growing interest in the deleterious effects of sedentary behaviour on lower‐limb arterial health. To permit further investigation, including larger epidemiological studies, there is a need to identify lower‐limb arterial health assessment tools that are valid and reliable, yet simple to administer. In this study, we sought to determine the validity and between‐day reliability of femoral–ankle pulse‐wave velocity (faPWV) measures obtained using an oscillometrically based device (SphygmocCor XCEL) in supine and seated positions. Doppler ultrasound was used as the criterion. A total of 47 healthy adults were recruited for validity ( n  = 32) and reliability ( n  = 15) analyses. Validity was determined by measuring faPWV in seated and supine positions using the XCEL and Doppler ultrasound devices, in a randomized order. Between‐day reliability was determined by measuring seated and supine faPWV using the XCEL on three different mornings, separated by a maximum of 7 days. The validity criterion [absolute standard error of estimate (aSEE) < 1.0 m s −1 ] was met in the supine [aSEE = 0.8 m s −1, 95% confidence interval (CI) 0.4–1.0], but not in the seated (aSEE = 1.2 m s −1, 95% CI 1.1–1.2) position. Intraclass correlation coefficient (ICC) estimates revealed that the XCEL demonstrated good reliability in the supine position (ICC = 0.83, 95% CI 0.65–0.93), but poor reliability in the seated position (ICC = 0.29, 95% CI 0.23–0.63). The oscillometric XCEL device can be used to determine lower‐limb pulse‐wave velocity with acceptable validity and reliability in the conventionally recommended supine position, but not in the seated position. Abstract :